Sharia Motivation and Internal Control on the Performance of Zakat Management Organizations - Mufidah Mufidah; Amri Amir; Achmad Hizazi; Enggar Diah Puspa Arum (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
This study examined the impact of sharia motivation and internal control on non-profit organization performance during the Covid Pandemic. The study’s novelty stems from the discovery of a new metric for sharia motivation. Additionally, this study addresses environmental uncertainty caused by the covid pandemic condition in a specific institutional setting, namely the zakah management organization. Thus, the pandemic weakens the economy; almost all industries are negatively impacted, but some have positive or increasing impacts, most notably the health industry; however, some industries have no effect, such as not-for-profit institutions, particularly zakah institutions that help a lot of people. As a result, environmental uncertainty was examined as a moderator variable. This study analyzed 90 observations from 20 zakah organizations in Jambi Province using cross-section data and primary data sources. SEM-PLS is a technique for performing moderating analysis. Sharia motivation and internal control affect on organizational performance while environmental uncertainty has no effect as a moderating variable. In addition, organizational performance affects accountability.